2014
DOI: 10.2147/jbm.s67989
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between red blood cell distribution width and blood pressure in patients with type 2 diabetes mellitus in Lagos, Nigeria

Abstract: BackgroundHigh red blood cell distribution width (RDW) is related to impairment of erythropoiesis, reflecting chronic inflammation and increased levels of oxidative stress, both of which are telltale signs of type 2 diabetics. The aim of this study was to evaluate the relationship between the RDW and fasting blood sugar/blood pressure, and compare the results from diabetics with nondiabetic controls.MethodsThis was an unmatched case-control study involving 200 participants consisting of 100 diabetics and 100 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
(33 reference statements)
0
11
0
Order By: Relevance
“… 22 , 36 – 39 This is due to the fact that high RDW indicates impairment of erythropoiesis, reflecting chronic inflammation and increased levels of oxidative stress, both of which are significant signs of T2DM that result in the RBC size variation. 40 In contrary, studies in Turkey and Nigeria reported that significant difference was not observed between cases and controls in RDW level. 39 , 40 Differences in study design and ethnic and cultural differences across the study populations may account for the variability of RDW across studies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 22 , 36 – 39 This is due to the fact that high RDW indicates impairment of erythropoiesis, reflecting chronic inflammation and increased levels of oxidative stress, both of which are significant signs of T2DM that result in the RBC size variation. 40 In contrary, studies in Turkey and Nigeria reported that significant difference was not observed between cases and controls in RDW level. 39 , 40 Differences in study design and ethnic and cultural differences across the study populations may account for the variability of RDW across studies.…”
Section: Discussionmentioning
confidence: 93%
“… 40 In contrary, studies in Turkey and Nigeria reported that significant difference was not observed between cases and controls in RDW level. 39 , 40 Differences in study design and ethnic and cultural differences across the study populations may account for the variability of RDW across studies.…”
Section: Discussionmentioning
confidence: 93%
“…There is a defect in insulin effect, secretion or both [1,2]. As obesity and sedentary life style is common in the society, DM type 2 frequency is increasing [3].…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of DM; 1) type I diabetes that is commonly observed in children and adults and is related to insulin defects, and 2) type II diabetes that occurs in adults and accounts for more than 90% of all cases of diabetes in the world. The risk factors for type 3 diabetes include low activity, obesity, and aging (6). Nowadays, type 2 diabetes is one of the most common and complicated problems of the community.…”
Section: Introductionmentioning
confidence: 99%